Tinjauan Kinerja Keuangan: Analisis Current Ratio dan Debt to Equity Ratio Terhadap Return on Equity dalam Industri Tekstil dan Garmen di Bursa Efek Indonesia (BEI) - Furniawan Furniawan (Universitas La Tansa Mashiro, 2022)
This research aims to provide a comprehensive overview of financial performance in the textile and garment industry on the Indonesia Stock Exchange (IDX) through the analysis of two key financial ratios: Current Ratio (CR) and Debt to Equity Ratio (DER). The study focuses on understanding the implications of these ratios on the Ratio on Equity (ROE). Data from financial statements of selected textile and garment companies listed on the IDX are collected and analyzed over a specific period. The Current Ratio assesses a company's short-term liquidity, measuring its ability to meet short-term obligations. On the other hand, Debt to Equity Ratio evaluates the proportion of debt in a company's capital structure, indicating its financial leverage. The study investigates how variations in these ratios impact the Ratio on Equity, a critical indicator of overall financial health. The findings of this research will contribute to a better understanding of the financial dynamics within the textile and garment industry, aiding investors, analysts, and stakeholders in making informed decisions. By exploring the intricate relationships between Current Ratio, Debt to Equity Ratio, and Ratio on Equity, the study sheds light on potential risk factors and financial stability within the industry.